Systematic Literature Review On Challenges Against The Care Of The Elderly With Dementia - Nor Hanim, Awang @ Mohd Noor; Norfatiha, Othman; Nur Farrahanie, Ahmad Tarmizi; Faiz, Masnan; Nurhidayah, Marzuki @ Yahaya; Leha, Saliman (Auricle Global Society of Education and Research, 2024)
Elderly people aged 60 years and above and diagnosed with dementia need careful care from their family members or caregivers. The caregivers of the elderly with dementia face many challenges that must be overcome. This paper aims to discuss the conceptual definition of dementia and the challenges faced by caregivers when looking after the elderly with dementia.The secondary analysis method is used in this paper to find out the definition of the concept of dementia and the various challenges faced by caregivers from various sources in a secondary approach. The results of the study obtained from previous studies found four challenges faced by caregivers in caring for the elderly with dementia, namely limited communication, pressure on caregivers, the role of women in parental care and financial burden. The implication is that the roleof a caregiver who takes care of the elderly with dementia can cause internal conflict on the caregiver himself due to the decline in cognitive function among dementia patients.